Cerebral oxygenation and blood flow in term infants during postnatal transition: BabyLux project. Issue 6 (13th May 2019) - De Carli, Agnese; Andresen, Björn; Giovannella, Martina; Durduran, Turgut; Contini, Davide; Spinelli, Lorenzo; Weigel, Udo Michael; Passera, Sofia; Pesenti, Nicola; Mosca, Fabio; Torricelli, Alessandro; Fumagalli, Monica; et al.
Abstract : Objectives: A new device that combines, for the first time, two photonic technologies (time-resolved near-infrared spectroscopy and diffuse correlation spectroscopy) was provided and tested within the BabyLux project. Aim was to validate the expected changes in cerebral oxygenation and blood flow. Methods: A pulse oximeter and the BabyLux device were held in place (right hand/wrist and frontoparietal region, respectively) for 10 min after birth in healthy term infants delivered by elective caesarean section. Pulse oximeter saturation (SpO2 ), cerebral tissue oxygen saturation (StO2 ) and blood flow index (BFI) were measured over time. Tissue oxygen extraction (TOE) and cerebral metabolic rate of oxygen index (CMRO2 I) were calculated. Results: Thirty infants were enrolled in two centres. After validity check of data, 23% of infants were excluded from TOE and CMRO2 I calculation due to missing data. As expected, SpO2 (estimate 3.05 %/min; 95% CI 2.78 to 3.31 %/min) and StO2 (estimate 3.95 %/min; 95% CI 3.63 to 4.27 %/min) increased in the first 10 min after birth, whereas BFI (estimate −2.84×10 −9 cm 2 /s/min; 95% CI −2.50×10 −9 to −3.24×10 −9 cm 2 /s/min) and TOE (estimate −0.78 %/min; 95% CI −1.12 to –0.45 %/min) decreased. Surprisingly, CMRO2 I decreased (estimate −7.94×10 −8 /min; 95% CI −6.26×10 −8 to −9.62×10 −8 /min). Conclusions: Brain oxygenation and BFI during transition were successfully and simultaneously obtained by the BabyLux device; no adverse effects were recorded, and the BabyLux device did not limit the standard care. The preliminary results from clinical application of the BabyLux device are encouraging in terms of safety and feasibility; they are consistent with previous reports on brain oxygenation during transition, although the interpretation of the decreasing CMRO2 I remains open. Trial registration number: NCT02815618 .